An expressivist response to the infinite regress of interpretation argument against legal interpretivism - Wieczorkowski, Michał (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The paper aims to address the Infinite Regress of Interpretation Argument against Legal Interpretivism by offering an expressivist defence. In this paper, Legal Interpretivism is understood as the view that determining the content of law requires interpreting its sources, where the correctness of interpretation depends on its alignment with the result of applying the proper method of interpretation to those sources. The Infinite Regress of Interpretation Argument posits that rules of interpretation necessitate further meta-rules for their application; these, in turn, necessitate further meta-meta rules, ad infinitum, rendering rules of interpretation incapable of grounding legal content. This line of reasoning leads to the conclusion that Legal Interpretivism ultimately collapses into a form of legal nihilism, suggesting that participants in legal discourse seeking to determine legal content are systematically in error. To counter this argument, the paper employs the division of linguistic labour thesis, which holds that the meaning of interpretive rules depends on what legal experts mean by them. Additionally, it utilizes a sceptical solution to the rule-following problem, suggesting that the function of meaning ascriptions is expressive rather than descriptive, which implies that meaning ascriptions do not require any foundational justifiers. Consequently, the paper argues that what legal experts mean by rules of interpretation halts the regress of interpretation. Ultimately, the paper concludes that by endorsing an expressivist stance, legal interpretivists can uphold their commitments without falling into legal nihilism.